The Implemetation of Contextual Redefinition Strategy for the Improvement of Reading Skill of STMIK STIKOM Indonesia’s Students - Maria Osmunda Eawea Monny; Ni Putu Dian Indra Pratiwi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
One way of improving understanding of English for Specific Purposes is through Contextual Redefinition Strategy (CRS). The implementation of CRS is meant to enhance the understanding of students of STMIK STIKOM Indonesia mostly in computers and business terms. The implementation of CRS is done through Classroom Action Research (CAR) in 3 stages of activities; those are pre-implementation, Middle Test (Cycle I) and Final Test (Cycle II). Besides, questionnaire is used with the purpose to know students’ attitude towards CRS’ implementation. The results of reading test on pre–implementation show that out of 40 students, there were 26 students did not get the lowest score 55 as the passing score of the college. After the explanation of CRS stages, middle and Final Tests tested the topics of reading texts on computers and business through search for clues in nearby words or sentences, and paragraphs of a text. Specific context clues that should be explicitly considered to understand the meaning of the sentences are definition/explanation, synonym/restatement, antonym/contrast, inference/general, and punctuation context. The results of Middle Test show that 22 students could get the score above 55, however most of students made mistakes in making redefinition based on inference/general and punctuation context. The results of Cycle II show that all students can score above 55. Besides, the results show that the students could improve their understanding for inference/general and punctuation context. The questionnaire shows that the students are motivated to acquire more and more vocabularies based on the needs for computer and business terms. The implementation of CRS does not only improve students’ ability to understand English based on its context but also enrich the vocabularies.